Antimicrobial Resistance and Virulence Factors of Escherichia coli in Cheese Made from Unpasteurized Milk in Three Cities in Brazil - Ribeiro, Laryssa Freitas [UNESP]; Barbosa, Mayhara Martins Cordeiro; Pinto, Fernanda de Rezende; Maluta, Renato Pariz; Oliveira, Monica Costa [UNESP]; Souza, Viviane de; Medeiros, Maria Izabel Merino de; Borges, Lucimara Antonio [UNESP]; Amaral, Luiz Augusto do [UNESP]; Fairbrother, John Morris (Mary Ann Liebert, Inc, 2016)
The production of cheeses from unpasteurized milk is still widespread in Brazil, even with a legal ban imposed on its marketing. The manufacture of this cheese is a public health problem, due to the use of raw milk and the poor hygienic conditions throughout the supply chain process. Contamination may occur from several sources and involve several different pathogenic microorganisms, such as Escherichia coli. The latter can cause different clinical manifestations depending on the pathotype involved. Furthermore, some isolates manifest antimicrobial resistance and may be a risk for public health. The purpose of the current study was to investigate the presence of potentially pathogenic E. coli in raw-milk cheese in Brazil and their possible risk to public health. A total of 83 cheeses were collected from three different cities and 169 E. coli isolates were characterized for the presence of enteropathogenic E. coli, Shigatoxigenic E. coli, enterotoxigenic E. coli, extraintestinal pathogenic E. coli (ExPEC) virulence genes, phylogenetic type, antimicrobial resistance, O serogroup, and pulsed-field gel electrophoresis. The number of samples positive for E. coli was highest in Aracaju (90.32%, 28/31). The prevalence of samples positive for potential ExPEC genes was similar for Uberaba and Aracaju (23.07%); the most prevalent ExPEC virulence genes were tsh, iucD, and papC. Isolates from Uberaba had a higher prevalence of resistance to tetracycline (38.46%), amoxicillin/clavulanic acid (58.85%), and ampicillin (61.54%) than the other cities. Overall, antimicrobial resistance genes tetB, bla(TEM), and bla(CMY-2) were the most prevalent genes (26.32%, 15.79%, and 28.95%, respectively) and the most prevalent serotypes were O4 (8%), 018 (12%), and O23 (8%). Clones originating from the same regions and from different regions were observed. These results emphasize the presence of a potential danger for humans in the consumption of raw-milk cheeses in three cities in Brazil due to the presence of antimicrobial resistance, which should be monitored.